The feasibility and outcome of a community-based primary prevention program for cardiovascular disease in the 21st century - Kuneinen Susanna M; Eriksson Johan G; Kautiainen Hannu; Ekblad Mikael O; Korhonen Päivi E (TAYLOR & FRANCIS LTD, 2022)
Objective There is no evidence that systematic screening and risk factor modification in an unselected, asymptomatic population will reduce cardiovascular disease (CVD) mortality. This study aimed to evaluate the effectiveness of a primary care CVD prevention program on mortality during a 13-year follow-up. Design A risk factor survey was sent, followed by a nurse-led lifestyle counselling to respondents with at least one CVD risk factor, and a general practitioner's (GP) appointment for high-risk persons. Screening and interventions were performed during 2005-2006. Setting A public health care centre in the town of Harjavalta, Finland. Subjects All home-dwelling 45-70-year old inhabitants without manifested CVD or diabetes. Main outcome measures All-cause and CVD mortality. Results Altogether 74% (2121/2856) inhabitants responded to the invitation. The intervention was received by 1465 individuals (52% of the invited population): 398 risk persons had an appointment with a nurse, followed by an appointment with a GP for 1067 high-risk persons. During the follow-up, 370 persons died. Mortality among the non-respondents was twofold compared to the participants'. In subjects who received the intervention, the age- and gender-adjusted hazard ratio for all-cause mortality was 0.44 (95% CI: 0.36 to 0.54) compared to the subjects who did not receive the intervention. Conclusions Reducing mortality is possible in a primary care setting by raising health awareness in the community with screening, by targeted lifestyle counselling and evidence-based preventive medication for persons at high risk for CVD. Subjects not willing to participate in health surveys have the worst prognosis.